2020
DOI: 10.1161/strokeaha.119.028022
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Participation in the Chronic Disease Self-Management Program

Abstract: Background and Purpose: Self-management programs may improve quality of life and self-efficacy for stroke survivors, but participation is low. In a randomized controlled trial of a complex, multidisciplinary, team-based secondary stroke prevention intervention, we offered participants Chronic Disease Self-Management Program (CDSMP) workshops in addition to clinic visits and home visits. To enhance participation, workshops were facilitated by community health workers who were culturally and linguist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…We found that initiation is subpar among women with children. This finding aligns with those of Lin et al who noted that although participants were intrinsically motivated to participate, external factors such as increased life chaos were associated with lower attendance (44). Life with children can be busy, and the schedules of parents may not permit the addition of a weekly commitment (44).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that initiation is subpar among women with children. This finding aligns with those of Lin et al who noted that although participants were intrinsically motivated to participate, external factors such as increased life chaos were associated with lower attendance (44). Life with children can be busy, and the schedules of parents may not permit the addition of a weekly commitment (44).…”
Section: Discussionsupporting
confidence: 91%
“…This finding aligns with those of Lin et al who noted that although participants were intrinsically motivated to participate, external factors such as increased life chaos were associated with lower attendance (44). Life with children can be busy, and the schedules of parents may not permit the addition of a weekly commitment (44). Future interventions can improve participation among those with children by making provision for child care either onsite or through renumeration for childminding services.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to the barriers in this review, participants reported difficulty affording transport to attend such lifestyle programmes and were unable to participate in programmes that required fees not covered by health insurance 123 . Further, chronic disease management programmes that offered incentives also found participants were more willing to engage and experienced improved health outcomes 124–126 . This review suggests that free/affordable programmes can alleviate the financial burden and provide equal opportunities for individuals, regardless of their financial situation to participate.…”
Section: Discussionmentioning
confidence: 54%
“…whereas those with higher chaos scores attended fewer sessions. 41 This suggests that addressing key social determinants of health may enhance participation.…”
Section: Discussionmentioning
confidence: 99%
“…We recently found that individuals with higher numbers of clinic and home visits, moderately severe disability, and later enrollment in the study (ie, after we began offering incentives and transportation) attended more CDSMP sessions, whereas those with higher chaos scores attended fewer sessions. 41 This suggests that addressing key social determinants of health may enhance participation.…”
Section: Discussionmentioning
confidence: 99%